2011
DOI: 10.1590/s1413-70542011000600020
|View full text |Cite
|
Sign up to set email alerts
|

Organic production of red wine grapes under plastic cover in subtropical region of Brazil

Abstract: A trial was carried out aiming to evaluate the development and yield of red wine grapevines under plastic cover in an organic production system in Guarapuava, the Central-Southern region of Paraná State, Brazil. The experimental design was in a randomized blocks, in a 5x2 factorial arrangement (cultivars x rootstocks), with five red wine vine cultivars (Merlot, Malbec, Carbenet Sauvignon, Ives and Early Isabella) and two rootstocks (Paulsen 1103 e VR 043-43). The grafted grapevines were planted in September of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
(16 reference statements)
2
3
1
Order By: Relevance
“…These values are in accordance with the 15.3 °Brix found by Orlando et al (2003), higher than the 13.8 and 14.4°Brix observed by Botelho et al (2011) but lower than the 19.0° Brix observed at Bswh climate regions by Leão et al (2010). Clone 8 distinguished itself by presenting the highest values for total soluble solids.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These values are in accordance with the 15.3 °Brix found by Orlando et al (2003), higher than the 13.8 and 14.4°Brix observed by Botelho et al (2011) but lower than the 19.0° Brix observed at Bswh climate regions by Leão et al (2010). Clone 8 distinguished itself by presenting the highest values for total soluble solids.…”
Section: Resultssupporting
confidence: 91%
“…The mean production cycle (from start of budburst to harvest) in the three harvest seasons was 142 days (Table 2), similar to the 149 days observed by Orlando Botelho et al (2011). The highest temperatures and lowest rainfall observed in the 2013 growing season may have contributed to the reduction of the production cycle of the clones during this season (Smart and Robinson, 1991).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Besides elimination of negative effects like rain and diseases during grapevine growing season, the polyethylene cover has also shown to cause early ripening (Çoban, 2007) or delay harvest of grapes (Cangi et al, 2011;Kamiloglu et al, 2011). Furthermore, these studies have also revealed that microclimate alteration promoted by protected cultivations of grapevine has improved gas exchange and vine water status (Chavarria et al, 2008) and grape composition (Botelho et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…This recent innovation has been adopted in some Brazilian vineyards. The use of polyethylene cover in the vineyard has become widespread by wine grape growers to prevent diseases development, to reduce the use of fungicides, to increase the wine grape yield during the rainy summer and has also enabled organic table and wine grape production (Botelho et al, 2011;Pedro et al, 2011). Besides elimination of negative effects like rain and diseases during grapevine growing season, the polyethylene cover has also shown to cause early ripening (Çoban, 2007) or delay harvest of grapes (Cangi et al, 2011;Kamiloglu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%